Synthesis and effects of substrate temperature on ac and dc electrical properties of Cobalt Phthalocyanine (CoPc) thin films - (:unkn) unknown (AMER INST PHYSICS, 2007)
In this study, 4,4',4-[benzene-1,3,5-tryltris(oxy)]tri-9,10,16,17,23,24-hexa(hexylthio)phthalocyaninatocobalt(II) has been synthesized from 4-[3,5-bis(3,4-dicyano phenoxy)phenoxy]phthalonitrile and 4,5-bishexylthiophthalonitrile with CoCl2 center dot 6H(2)O in ethylene glycol at 170-180 degrees C for 6 hours. The effects of substrate temperature (during coating of the films) on the electrical characteristics were investigated. CoPc thin films were prepared by cast coating method at the substrate temperatures of 298, 348, 373, 398 K on interdigital gold electrodes on glass substrate. The dc and ac electrical properties of CoPc films were investigated in the temperature range of 298 - 391 K in dark. The ac electrical properties of CoPc films have been studied in the frequency range from 40 Hz to 100 kHz. All measurements were performed under N-2 flow. The temperature dependence of dc conductivity show typical Arrehenius behavior for all films. As the substrate temperature increases during coating of the films from 298 K to 398 K, the activation energy decreases from 1.04 to 0.96 eV. The ac conductivity of the films is represented by the form omega(s). The temperature dependency of frequency exponents on temperature suggests a correlated barrier hopping (CBH).
Keywords: dc conductivity; ac conductivity; correlated barrier hopping; Cobalt Phthalocyanine; GAS-SENSING PROPERTIES; CONDUCTION; ZNPC